Optimalisasi Peran Pemuda dalam Pelestarian Lingkungan Hidup melalui Pembelajaran Pancasila dan Lingkungan - Chandra, Febrian; Putri Febriani, Widia; Marlina, Leni; Elviyola; Elang Buana, Ikra; Eka Nopia, Risa (PT. Meja Ilmiah Publikasi, 2025)
Youth play a strategic role in environmental conservation as part of sustainable development. This article discusses the optimization of youth participation in environmental preservation through Pancasila and environmental learning. This community service program was conducted in Talang Kawo, Dusun Bangko, involving students and the local community in educational activities and concrete actions such as reforestation and waste management. The results showed an increase in youth awareness and participation in maintaining cleanliness and environmental sustainability. By integrating Pancasila values, youth are encouraged to take responsibility and actively contribute to environmental conservation efforts. This approach has proven effective in enhancing environmental awareness and shaping youth character as agents of change in ecosystem sustainability.